An In Vitro Evaluation of the Biological Effects of Carbon Nanotube-Coated Dental Zirconia. (20th August 2013) - Kou, Wen; Akasaka, Tsukasa; Watari, Fumio; Sjögren, Göran
Abstract : The purpose of this study is to evaluate functionalized multiwalled carbon nanotubes (fMWCNTs) as a potential coating material for dental zirconia from a biological perspective: its effect on cell proliferation, viability, morphology, and the attachment of an osteoblast-like cell. Osteoblast-like (Saos-2) cells were seeded on uncoated and fMWCNT-coated zirconia discs and in culture dishes that served as controls. The seeding density was 10 4  cells/cm 2, and the cells were cultured for 6 days. Cell viability, proliferation and attachment of the Saos-2 cells were studied. The results showed that Saos-2 cells were well attached to both the uncoated and the fMWCNT-coated zirconia discs. Cell viability and proliferation on the fMWCNT-coated zirconia discs were almost the same as for the control discs. Better cell attachment was seen on the fMWCNT-coated than on the uncoated zirconia discs. In conclusion, fMWCNTs seem to be a promising coating material for zirconia-based ceramic surfaces to increase the roughness and thereby enhance the osseointegration of zirconia implants.